HUBUNGAN POWER OTOT LENGAN BAHU DENGAN KEMAMPUAN SERVIS ATAS PADA TIM BOLA VOLI PUTRA SMA NEGERI 1 PANYABUNGAN - Ahmad Ginda Sakti; Drs. Saripin, M.Kes, AIFO '; Ni Putu Nita Wijayanti, S.Pd, M.P.d (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrak,: The problem in this research is the lack of volleyball team of SMA Negeri 1 Payabungan ability in floating overhand serve, this research was conducted to know whether or not there is a correlation between shoulder arms muscle power with the floating overhand serve in playing volleyball in SMA Negeri 1 Panyabungan .The sample of this research is the volleyball team of SMA Negeri 1 Panyabungan which consisted of 12 persons.The outhor used total sampling technique in collecting the data. The outhor also used two-hand medicine ball put test as the instrument tomeasuring shoulder arms muscle power and two-hand medicine ball put test to measuring the ability to direct the ball towards to the goal properly. Then, the data was analyzed statistically, to test the normality at significant level 0,05α in liliefors test. The hypothesis is there is the significant correlationbetween shoulder arms muscle power with the floating overhand serve in playing volleyball in SMA Negeri 1 Panyabungan.Based on the analysis of liliefors test, Lcount (x) is 0.1743dan Ltabel 0.242, Lcount (y) is 0.1587dan Ltabel 0,242, that means Lcount < Ltabel, and therefore, the sample of the research was normal distribution population. Then based on the analysis from product moment correlation counting correlation between shoulder arms muscle power with the floating overhand serve, the writer got the mean score of shoulder arms muscle poweris 4.55 with the standard deviation 0.31, floating overhand servemean score is 18.92, standard deviation 4.40 and from the correlation analysis “r” in product moment (rxy) is rcount= 0.409. The writer concluded that was a correlation between shoulder arms muscle power with the floating overhand serve, which correlation coefficient can be seen form the correlation interpretation “r” has a mediocre correlation level with the interpretation value r 0,40 – 0,599.Key Words: Shoulder Arms Muscle Power, Floating Overhand Serve